Berberine Protects against Palmitate-Induced Endothelial Dysfunction: Involvements of Upregulation of AMPK and eNOS and Downregulation of NOX4. (9th December 2013) - Zhang, Ming; Wang, Chun-Mei; Li, Jing; Meng, Zhao-Jie; Wei, Sheng-Nan; Li, Ji; Bucala, Richard; Li, Yu-Lin; Chen, Li
Abstract : Endothelial dysfunction is a critical factor during the initiation of cardiovascular complications in diabetes. Berberine can ameliorate endothelial dysfunction induced by diabetes. However, the underlying mechanisms remain unclear. The aim of this study was to investigate the protective effect and mechanism of berberine on palmitate-induced endothelial dysfunction in human umbilical vein endothelial cells (HUVECs). The cell viability of HUVECs was determined by MTT assays. Nitric oxide (NO) level and production of reactive oxygen species (ROS) were determined in supernatants or in the cultured HUVECs. The mRNA level of endothelial nitric oxide synthase (eNOS) was measured by RT-PCR, and the protein levels of eNOS, p-eNOS, Akt, p-Akt, AMPK, p-AMPK, and NADPH oxidase (NOX4) were analyzed. The results demonstrated that berberine significantly elevated NO levels and reduced the production of ROS. The expressions of eNOS were significantly increased, while NOX4 protein expression was decreased in berberine-treated HUVECs. Moreover, berberine upregulated the protein expression of AMPK and p-AMPK in palmitate-treated HUVECs, but had no effect on the levels of Akt. Therefore, berberine ameliorates palmitate-induced endothelial dysfunction by upregulating eNOS expression and downregulating expression of NOX4. This regulatory effect of berberine may be related to the activation of AMPK.